Unveiling Impulsive Buying Behavior During E-Commerce Discount Events Among College Students - Rafsanjani, Mohamad Arief; Wulandari, Siti Sri; Wardoyo, Dewie Tri Wijayati; Soesatyo, Yoyok; Srisuk, Prattana; Saphira, Hanandita Veda (IKIP Widya Darma Surabaya, 2025)
Objective: This study explores the factors influencing impulsive buying behavior among students during discount events on e-commerce platforms. Method: This study using a qualitative phenomenological approach, then in-depth interviews were conducted with ten active students who have participated in at least two discount events in the past six months. Results: The study evidence that large discounts create a sense of increased value, while FOMO (fear of missing out) and social influences heighten the urgency to buy. Additionally, the intuitive design of e-commerce apps facilitates impulsive buying and emotional outcomes such as satisfaction and regret, illustrating the complexity behind these decisions. According to the current research findings, e-commerce platforms are encouraged to integrate features that promote more mindful shopping, while financial literacy initiatives targeting students are recommended. Furthermore, governments could consider regulations to limit excessive promotional practices and ensure greater consumer transparency. Novelty: This study contributes to understanding impulsive buying behavior, offering insights for creating a healthier and more sustainable shopping ecosystem for young consumers.